Teachers’ Strategies in Fostering Civic Values through Inquiry Learning: A Qualitative Study on Civic Education in Elementary School - Saputri, Sefit; Hardiyati, Mikyal (Yayasan Zia Salsabila, 2024)
Citizenship issues in elementary school students are increasingly complex along with social and digital developments. This study aims to examine teachers' strategies in fostering citizenship values through an inquiry learning approach in the context of Citizenship Education in elementary schools. The research used a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation, and data analysis assisted by NVivo 14 software. The research setting was several primary schools in Kendari City, with the main informants consisting of class teachers, principals, and students. The results showed that teachers implemented five main strategies, namely the use of contextual triggering questions, facilitation of exploration and critical discussion, collaborative reflection on values, participatory citizenship projects, and exemplary values by teachers. These strategies contributed significantly to increasing students' awareness, democratic attitudes and active participation in school life. The findings suggest that the inquiry approach is effective in shaping civic literacy from an early age. This research provides theoretical contributions to value-based pedagogical approaches, as well as practical implications for teachers and policy makers in designing more contextual, reflective and transformative civic learning in primary schools.